THE ROLE OF LOCAL INSTITUTIONS AND SOCIAL CAPITAL IN STRENGTHENING COLLABORATIVE GOVERNANCE OF TLOCOR MARINE TOURISM, INDONESIA - Hendra Sukmana; Agus Subianto; Viv Djanat Prasita; Sri Umiyati (International Journal Multidisciplinary (IJMI), 2026)
Objective: This study examines the role of local institutions and social capital in sustaining collaborative governance in Tlocor Marine Tourism, a community-based coastal tourism destination in Sidoarjo Regency, Indonesia. Method: A qualitative case study approach was employed through in-depth interviews, observations, and document analysis. Data were analyzed using the Collaborative Governance Regime (CGR) framework of Emerson, Nabatchi, and Balogh, focusing on principled engagement, shared motivation, and capacity for joint action. Results: The findings show that collaborative governance in Tlocor is supported by active stakeholder engagement involving village government, BUMDes, Pokdarwis, local communities, government agencies, universities, and other actors. Principled engagement is facilitated through formal and informal communication that promotes dialogue, consensus-building, and collective problem-solving. Shared motivation is strengthened by social capital, particularly trust, mutual cooperation (gotong royong), collective ownership, and social solidarity, which encourage community participation in tourism governance. Capacity for joint action is supported by the complementary roles of BUMDes Mitra Abadi and Pokdarwis in providing leadership, coordination, resource mobilization, and operational support. Novelty: The study concludes that sustainable coastal tourism governance depends not only on formal institutional arrangements but also on the integration of local institutions and community-based social capital. Strengthening trust-based relationships and local institutions is therefore essential for sustaining collaborative governance and tourism development.